In vitro antioxidant and anti-inflammatory effects of Erythroxylum cuneatum leaf extract on oxidized low-density lipoprotein-stimulated human aortic endothelial cells - Adam, Siti Khadijah; Shanmugam, Nitya; Mohamad, Sharlina; Abd Rahman, Shamima; Mohd Moklas, Mohamad Aris (SAGE Publications, 2023)
Background: The oxidation of low-density lipoprotein (LDL) by reactive oxygen species (ROS) causes inflammation, which results in the expression of adhesion molecules and monocyte adhesion and migration. This eventually leads to the progression of atherosclerosis. Erythroxylum cuneatum (EC), locally known as “Chinta mula,” is used as traditional medicine in certain countries. However, the scientific evidence of its medicinal properties, particularly related to cardiovascular disease (CVD) is still limited. Objectives: This study was designed to evaluate the antioxidant and anti-inflammatory properties of EC leaf extract in protecting against atherosclerosis in vitro. Materials and Methods: Human aortic endothelial cells (HAoECs) induced by oxidized LDL (oxLDL) were treated with comparable concentrations (40 and 80 µg/ml) of EC ethanol and acetone leaf extracts. The antioxidant activities were determined by thiobarbituric acid reactive substances (TBARS), ROS, and nitric oxide (NO) production assays. The anti-inflammatory effects of EC leaf extract were evaluated using monocyte adhesion and migration assays and the expression of adhesion molecules, namely, intracellular adhesion molecule-1 (ICAM-1) and human vascular cell adhesion molecule-1 (VCAM-1). Results: Both EC extracts possess antioxidant and anti-inflammatory activities against oxLDL-induced HAoECs, which were concentration-dependent. Acetone extract showed significant reduced TBARS levels and increased NO production compared to ethanol extract. It also caused a significant decrease in monocyte adhesion and expression of ICAM-1 as compared to ethanol extract. Conclusion: These findings suggest that EC leaf extract is valuable in preventing atherogenesis. The superior effect of EC acetone extract warrants future studies to elucidate its mechanisms in the prevention of CVDs, particularly atherosclerosis.